Uncoupling of neurogenesis and differentiation during retinal development. (3rd March 2017) - Engerer, Peter; Suzuki, Sachihiro C; Yoshimatsu, Takeshi; Chapouton, Prisca; Obeng, Nancy; Odermatt, Benjamin; Williams, Philip R; Misgeld, Thomas; Godinho, Leanne
Abstract: Conventionally, neuronal development is regarded to follow a stereotypic sequence of neurogenesis, migration, and differentiation. We demonstrate that this notion is not a general principle of neuronal development by documenting the timing of mitosis in relation to multiple differentiation events for bipolar cells (BCs) in the zebrafish retina using in vivo imaging. We found that BC progenitors undergo terminal neurogenic divisions while in markedly disparate stages of neuronal differentiation. Remarkably, the differentiation state of individual BC progenitors at mitosis is not arbitrary but matches the differentiation state of post‐mitotic BCs in their surround. By experimentally shifting the relative timing of progenitor division and differentiation, we provide evidence that neurogenesis and differentiation can occur independently of each other. We propose that the uncoupling of neurogenesis and differentiation could provide neurogenic programs with flexibility, while allowing for synchronous neuronal development within a continuously expanding cell pool. Synopsis: Investigating the timing of developmental hallmarks of a molecularly defined progenitor population in the retina reveals that mitotic divisions do not occur at a specific time in a cell's differentiation trajectory, but that neurogenesis and differentiation are uncoupled. Timing of developmental hallmarks in a CNS progenitor population tracked in vivo . The differentiation status of terminally dividing progenitors at mitosis varies greatly as cell cycle and differentiation are uncoupled. Progenitor differentiation state is in lock‐step with post‐mitotic surrounding cells. Abstract : In vivo cell lineage tracking shows that developing neurons in the zebrafish retina do not adhere to a stereotypic neurogenesis‐migration‐differentiation sequence, but that there is unexpected flexibility in neurodevelopmental programs.